2020
DOI: 10.1111/1751-7915.13708
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of active ingredients of a commercial aflatoxin biocontrol product in naturally occurring fungal communities across Kenya

Abstract: Human populations in Kenya are repeatedly exposed to dangerous aflatoxin levels through consumption of contaminated crops. Biocontrol with atoxigenic Aspergillus flavus is an effective method for preventing aflatoxin in crops. Although four atoxigenic A. flavus isolates (C6E, E63I, R7H and R7K) recovered from maize produced in Kenya are registered as active ingredients for a biocontrol product (Aflasafe KE01) directed at preventing contamination, natural distributions of these four genotypes prior to initiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 66 publications
(148 reference statements)
2
8
0
Order By: Relevance
“…At the same time, these populations consisted of both locally restricted and widely dispersed common haplotypes among samples and among countries. Second, complete LD was observed in all countries (Table 2, Figure S4), supporting clonal evolution of A. flavus populations in southern Europe, as seen in other studies of natural populations of A. flavus (Grubisha & Cotty, 2015;Hadrich et al, 2013;Islam et al, 2018Islam et al, , 2020Ortega-Beltran et al, 2020;Picot et al, 2018). Finally, members of the VCG to which MUCL54911 belongs occur in all the sampled regions (Table 4), revealing a natural distribution of this biocontrol agent across southern Europe and opening the potential for use of MUCL54911 in the mitigation of aflatoxin contamination throughout this region.…”
Section: Discussionsupporting
confidence: 84%
“…At the same time, these populations consisted of both locally restricted and widely dispersed common haplotypes among samples and among countries. Second, complete LD was observed in all countries (Table 2, Figure S4), supporting clonal evolution of A. flavus populations in southern Europe, as seen in other studies of natural populations of A. flavus (Grubisha & Cotty, 2015;Hadrich et al, 2013;Islam et al, 2018Islam et al, , 2020Ortega-Beltran et al, 2020;Picot et al, 2018). Finally, members of the VCG to which MUCL54911 belongs occur in all the sampled regions (Table 4), revealing a natural distribution of this biocontrol agent across southern Europe and opening the potential for use of MUCL54911 in the mitigation of aflatoxin contamination throughout this region.…”
Section: Discussionsupporting
confidence: 84%
“… a Allele sizes indicate amplicon size in base pairs as called on an ABI 3730 DNA Analyzer with the LIZ500 standard (Applied Biosystems). Islam et al (2021) previously published data of Aflasafe KE01. However, the haplotype name and allele size of AF66 for active ingredient E63-I has been corrected in the Table.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, when the atoxigenic isolates were genotyped with SSR markers, a few SSR genotypes occurred in high frequency and in several provinces demonstrating wide distribution and hence potential of high adaptation in the country ( Table 3 ; Supplementary Table S1 ). An extensive Aspergillus population distribution study in Kenyan soil showed that the active ingredients of the biocontrol product Aflasafe KE01 are widely distributed in Kenya ( Islam et al, 2021 ). Isolates of some representative Burundi-specific SSR groups detected in the current study were tested in laboratory assays as potential candidates for the development of biocontrol products for aflatoxin management for use in Burundi ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The residual influences of biocontrol products can be assessed by the multi-year monitoring of the AF- active ingredients in agricultural soils. This can be done by examining individual genotypes within the resident fungal population and characterizing those individuals with either culture-based (i.e., a vegetative compatibility analysis (VCAs) [ 20 , 50 ] or molecular tools, such as microsatellite analyses or SNP monitoring with pyrosequencing [ 51 , 52 , 53 ]. Moreover, several studies have previously identified the role of some aflatoxin biosynthesis pathway genes, such as omt -A and aflR , to develop new approaches to estimate the aflatoxin-producing capacity of Aspergillus spp., such as the use of real-time PCR [ 54 , 55 , 56 ].…”
Section: Introductionmentioning
confidence: 99%